2008
DOI: 10.1016/j.exger.2008.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Zinc deficiency and IL-6 −174G/C polymorphism in old people from different European countries: Effect of zinc supplementation. ZINCAGE study

Abstract: IL-6 SNP at position -174 is associated with age-related diseases characterized by an impaired Zn status. This polymorphism seems also relevant in regulating the expression of proteins, such as Metallothioneins (MT), involved in the modulation of Zn homeostasis. Since high IL-6 levels in elderly induce hypozinchemia, the IL-6-174 SNP may be useful to identify old subjects who are at risk for Zn deficiency. The objectives of this study are: (1) to choose old subjects who effectively need Zn supplementation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 59 publications
2
57
0
1
Order By: Relevance
“…Interestingly, in this last study C-old and nonagenarian subjects display also impaired innate immune response (NK cell cytotoxicity) coupled with increased MTs, zinc deficiency and low zinc ion bioavailability in comparison with C+ carriers [56]. A functional implication of the IL-6 -174G/C locus on MT expression and zincregulated genes has been also recently confirmed by targeted studies with in vitro zinc supplementation [98] as well as in vivo [95,108].…”
Section: Zinc-interleukin-6 Gene Interactionsupporting
confidence: 56%
See 3 more Smart Citations
“…Interestingly, in this last study C-old and nonagenarian subjects display also impaired innate immune response (NK cell cytotoxicity) coupled with increased MTs, zinc deficiency and low zinc ion bioavailability in comparison with C+ carriers [56]. A functional implication of the IL-6 -174G/C locus on MT expression and zincregulated genes has been also recently confirmed by targeted studies with in vitro zinc supplementation [98] as well as in vivo [95,108].…”
Section: Zinc-interleukin-6 Gene Interactionsupporting
confidence: 56%
“…The main results of the project confirmed a strong contribution of MT genetic variants in regulating zinc homeostasis and perhaps its dietary requirements as well as their relevance in longevity and in some age-related pathologies [34,57,95,98]. Moreover, it has been confirmed that IL-6 -174 polymorphisms can be used to identify old subjects with higher risk to develop zinc deficiency [98,108]. The study revealed also that contradictory data existing on the association between IL-6 -174 polymorphisms and chronic disease can find a rationale in the different dietary intake of zinc existing in the different population studied [108].…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…110 (Z) 10 mg Zn as aspartate for 7 weeks Increased NK cell cytotoxicity (48,68) Old mice Male Balb/c 10 (C) 18 mg Zn as sulphate (22 mg/l in drinking water)…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%